Graphene : fundamentals and emergent applications - Warner, Jamie H. (Elsevier, 2013)
Providing fundamental knowledge necessary to understand graphene's atomic structure, band-structure, unique properties and an overview of groundbreaking current and emergent applications, this new handbook is essential reading for materials scientists, chemists and physicists. Since the 2010 physics Nobel Prize awarded to Geim and Novosolev for their groundbreaking work isolating graphene from bulk graphite, there has been a huge surge in interest in the area. This has led to a large number of news books on graphene. However, for such a vast inflow of new entrants, the current literature is surprisingly slight, focusing exclusively on current research or books on previous "hot topic" allotropes of carbon. This book covers fundamental groundwork of the structure, property, characterization methods and applications of graphene, along with providing the necessary knowledge of graphene's atomic structure, how it relates to its band-structure and how this in turn leads to the amazing properties of graphene. And so it provides new graduate students and post-docs with a resource that equips them with the knowledge to undertake their research. Discusses graphene's fundamental structure and properties, acting as a time-saving handbook for validated researchDemonstrates 100+ high-quality graphical representations, providing the reader with clear images to convey complex situationsReviews characterization techniques relevant to grapheme, equipping the reader with experimental knowledge relevant for practical use rather than just theoretical understanding